6(x-1)-3=3(x-4)

Simple and best practice solution for 6(x-1)-3=3(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-1)-3=3(x-4) equation:


Simplifying
6(x + -1) + -3 = 3(x + -4)

Reorder the terms:
6(-1 + x) + -3 = 3(x + -4)
(-1 * 6 + x * 6) + -3 = 3(x + -4)
(-6 + 6x) + -3 = 3(x + -4)

Reorder the terms:
-6 + -3 + 6x = 3(x + -4)

Combine like terms: -6 + -3 = -9
-9 + 6x = 3(x + -4)

Reorder the terms:
-9 + 6x = 3(-4 + x)
-9 + 6x = (-4 * 3 + x * 3)
-9 + 6x = (-12 + 3x)

Solving
-9 + 6x = -12 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-9 + 6x + -3x = -12 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-9 + 3x = -12 + 3x + -3x

Combine like terms: 3x + -3x = 0
-9 + 3x = -12 + 0
-9 + 3x = -12

Add '9' to each side of the equation.
-9 + 9 + 3x = -12 + 9

Combine like terms: -9 + 9 = 0
0 + 3x = -12 + 9
3x = -12 + 9

Combine like terms: -12 + 9 = -3
3x = -3

Divide each side by '3'.
x = -1

Simplifying
x = -1

See similar equations:

| X^4+x^3-20x^2=0 | | 2(x-5)+2=6x | | x^2-4x=x-3 | | 8373927+829283=x | | x^2-4c=x-3 | | 2x^2-6x+9=65 | | 0=w^3-2w^2-32-770 | | (-12)=x+7 | | x+ln(27-x^2)-2ln(x)=0 | | 14x-21=0 | | 16-6x=-8 | | 3(x+11)-2(x+2)=2(x-5)+3(x-7) | | 1/3x=-8/3+5/6 | | 11(x-4)=3x-90+7x | | c/4-5=4 | | 3(x+11)-2(x+2)=2(x-5)+2(x-7) | | 6b+4b+2b=144 | | 3x^2-27=2x^3+7x^2-18x-63 | | 3(y-10)=90 | | -3x^2=3x-9 | | 2(6-10N)=10(2N-6) | | 7x+3y=mfory | | y=-16t+236 | | 9(x-3)=3x-61+6x | | 4(5-2x)-1=6(4-x)-3x-5 | | 4(x-9)-3x=3(x-2)-4 | | 4(x+2)=5(x+6) | | F=8/5(n-27) | | 5(x+15)=10 | | 4x^2+16x-7=0 | | 3/5-3.6 | | x/7+3=6 |

Equations solver categories